THE INFLUENCE OF MARKETING MIX AND BRAND IMAGE ON BRAND EQUITY - นันตีสู้ จันทร์จิรา; ศรีบุญลือ อุมาวสี (RMUTT Global Business and Economics Review, 2018)
This objective of this research was to study the influence of marketing mix and brand image on brand equity. The samples used in this study were FUJI FLM or OLYMPUS mirrorless camera users in Bangkok Metropolitan area. The statistics used for data analysis were frequency, percentage, mean, and hypothesis testing including independent samples t-test, Simple Regression Analysis, and Multiple Regression Analysis at a significance level of 0.05. The research results revealed that the majority of respondents were female (69.00%), aged between 21-30 years. (80.75%), held a bachelor’s degree (88.75%), worked as employees at private companies (64.25%), and received monthly income between 15,0001-25,000 baht (64.25%). Moreover, it was found that marketing mix, brand image, and brand equity were at the highest level with averages of 4.64, 4.84, and 4.74 respectively. The results of hypothesis testing revealed that marketing mix and brand image correlated with brand equity. The results of multiple regression analysis also showed that marketing mix and brand image influenced brand equity. Finally, differences in brand significantly caused different perceptions in marketing mix, brand image, and brand equity at a significance level of 0.05.